The Future of Neuroimplantable Devices A Materials Science and Regulatory Perspective - Obidin, Nikita (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.